ICTO Service and Activity System with SMS - Adrian Forca (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
The study titled "Information and Communications Technology Office Service and Activity System with Short Messaging Service" focuses on improving the current processes of the Information and Communications Technology Office through the development of a comprehensive system. The researcher identified problems within the existing processes and drew inspiration from prior arts and the Iterative Software Process Model to develop the Platform with SMS Notification. To evaluate the effectiveness of the system, the researcher used the ISO 25010:20r15 Software Quality Instrument and employed a Descriptive Research Design. The feedback from the respondents justified the study's objectives, leading to the conclusion that all objectives were successfully met. The software was found to exhibit "Very High" effectiveness in terms of various Software Quality Characteristics. The study recommends the full implementation of the developed system in the operational environment of the University. This implementation would bring about an upgrade from manual to automated and paperless recording processes, facilitated by Information Technology solutions. Furthermore, the study encourages future researchers to enhance the developed system by incorporating better features and expanding its scope to cover additional processes. The Study utilized the refreshed servers from the existing information systems that contributes to the maximization of the available resource to its potential use.